2017
DOI: 10.3126/jpn.v7i1.16777
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of thyroid and its correlation with serological findings

Abstract: Background: Thyroid autoimmunity can cause several forms of thyroid disorders i.e. Grave's disease, Hashimoto's thyroiditis, atrophic autoimmune thyroiditis, post-partum thyroidits etc. Cytological diagnosis may be sometimes difficult is some cases. In such conditions, cytology along with serological tests aid at reaching a correct diagnosis. Hence, this study was undertaken to evaluate the serum level of anti-TPO antibody with respect to serum concentrations of thyroid hormones and its importance in diagnosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
2
1
1
Order By: Relevance
“…According to the study conducted in Maharajgnj, Nepal by Karki et al mean age of thyroid swelling was 40.4 years, which is in accordance to our study [14]. In the present study, the incidence of thyroid gland lesion was highest in 31-40 years age groups (39.1%) followed by 41-50 years (24.1%) and 51-60 years (14.9%) which is similar to the study done by Karki et al which showed 20-50 years as common age of thyroid gland swelling [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the study conducted in Maharajgnj, Nepal by Karki et al mean age of thyroid swelling was 40.4 years, which is in accordance to our study [14]. In the present study, the incidence of thyroid gland lesion was highest in 31-40 years age groups (39.1%) followed by 41-50 years (24.1%) and 51-60 years (14.9%) which is similar to the study done by Karki et al which showed 20-50 years as common age of thyroid gland swelling [14].…”
Section: Discussionsupporting
confidence: 91%
“…However, in contrast to present study, most patients were euthyroid in study conducted by Staii et al [13]. The sensitivity and specicity of Anti-TPO antibodies for diagnosing autoimmune thyroiditis was found to be 89.7% and 94.8% respectively which is higher compared to study conducted by Karki et al [14]. However Engler et al has reported 96% sensitivity of anti TPO antibody in autoimmune thyroiditis [19].…”
Section: Discussioncontrasting
confidence: 85%
“…This is justified by similar findings stated by Karki et al18 and Staii et al19 ,. Present study showed most commonly affected age is 41 -60 years which is comparable to the study done by Junu Devi et al17 and Poudel et al 12 .The study showed that 88% are non neoplastic lesion and 12% are neoplastic lesion whereas in study by Junu Devi et al17 , Choudhary R et al 3 and Chandanwale S et al 20 (neoplastic and non neoplastic cases were 4.55% and 94.95% respectively.…”
supporting
confidence: 84%
“…7 Although many persons with Hashimoto's thyroiditis are euthyroid, significant proportion of them develop hypothyroidism eventually. 8 The prevalence of Hashimoto's thyroiditis in elderly patients is estimated to be 40%. 9 However, diagnosis relies mostly on cytology and/or histology.…”
Section: Resultsmentioning
confidence: 99%